Investigation of the oxidation process in GeTe-based phase change alloy using Ge K-edge XANES spectroscopy - Krbal, Miloš; Kolobov, Alexander, V; Fons, Paul; Nitta, Kiyofumi; Uruga, Tomoya; Tominaga, Junji (Walter de Gruyter GmbH & Co. KG, 2019)
In this work, we clearly demonstrate the efficacy of using XANES spectroscopy in conjunction with a Pilatus detector as a sensitive tool to allow the study of the oxidation process in GeTe alloys via depth profile analysis. On the basis of Ge K-edge XANES spectra, it was found that GeTe alloys do not oxidize readily after an initial native surface oxidation that occurs upon exposure to oxygen in the air at the elevated temperatures, 100 degrees C and 330 degrees C. We demonstrate that amorphous GeTe possesses a higher predisposition to oxidation than crystalline GeTe when exposed to the air at temperature of 100 degrees C. When the temperature is set to 330 degrees C in an air ambient, we show that the amorphous to crystal phase transition affects the oxidation process more significantly than the simple annealing of crystalline GeTe. We suggest that the higher tendency of GeTe films to oxidize during the phase transition is a consequence of the breaking of Ge-Ge bonds in the presence of oxygen atoms which subsequently leads to the extra formation of Ge-O bonds during crystallization.
Studium oxidace ve slitině pro fázovou přeměnu obsahující GeTe s využitím XANES spektroskopie při absorpční hraně Ge K-hladiny
Keywords: local structure; oxidation; phase-change memory; SSC-2018; X-ray absorption spectroscopy; lokální struktura; oxidace; paměti na bázi fázové přeměny; SSC-2018; rentgenová absorpční spektroskopie